Re-examining The Correlation between Islam and Adat Through Environmental Conservation - Iis Badriatul Munawaroh (West Science Islamic Studies, 2023)
The involvement of indigenous peoples in environmental protection is of significant importance. Due to their profound affinity for the natural world, they assume a pivotal role in the forefront of environmental preservation efforts. Conversely, the cultural practices and traditions of indigenous communities frequently encounter conflicts with the doctrinal principles of prevailing religions, such as Islam. Individuals who continue to uphold the customs and practices of their forebears, with the intention of preserving the harmony of the cosmos, are frequently labelled as primitive, animistic, irreligious, and such. The objective of this study is to reexamine the correlation between the cultural practices of the indigenous community residing in Kampung Kuta and the Islamic faith, specifically in the context of their endeavours towards environmental preservation. This study argues that the interpretation of rituals and traditions through the lens of intersubjective relationships might establish a connection between these practices and the preservation of the environment, as well as the application of Islamic principles in daily existence. The utilization of pamali and pikukuh customs aligns with the Islamic principles of prohibiting harm (fasad) and the idea of Khalifah.  The significance of these two notions lies in their role in the conservation of the natural environment, as human behaviors influenced by their connection with nature have a direct impact on the current and future state of the environment.